DAMPAK PENERAPAN MEDIA INTERAKTIF TERHAADAP MOTIVASI BELAJAR SISWA - Ani Yulianti; Ghina Shalihah; Ismatul Hawa; Riska As Sevilla; Zulfa Huriah Dina Kazimah; Ahmad Suriansyah; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the impact of interactive learning media on the learning motivation of elementary school students through a systematic literature review. The problem underlying this study is the low utilization of interactive media in elementary education, which results in passive learning, limited student engagement, and declining motivation. The study aims to analyze types of effective interactive media, identify their influence on motivational aspects, and evaluate challenges in their implementation at the elementary school level. Using purposive sampling, this review synthesizes national journals, empirical studies, and educational literature published within the last ten years. The analysis shows that interactive media such as game based learning, interactive videos, simulations, augmented reality, and mobile learning applications significantly increase students’ attention, curiosity, confidence, satisfaction, and overall motivation. Visual stimulation, immediate feedback, and hands-on learning experiences make abstract concepts more concrete and meaningful. However, issues such as limited infrastructure, teacher digital competence, content quality, and classroom management challenges remain obstacles to optimal implementation. The study concludes that interactive media play a crucial role in enhancing intrinsic motivation and supporting active, student-centered learning. The findings highlight the need for continuous teacher training, equitable digital access, and contextually relevant media development to maximize the benefits of interactive learning in elementary schools.